2003
DOI: 10.1007/bf02723582
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counseling and prenatal diagnosis in India — experience at Sir Ganga Ram Hospital

Abstract: Advanced molecular, cytogenetic and biochemical techniques have been a useful addition for genetic counseling and prenatal diagnosis in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
2
10
1
1
Order By: Relevance
“…1 However, in this article, we shall concentrate on the misuse of prenatal technology, which has contributed to the skewed sex ratio in India.…”
mentioning
confidence: 99%
“…1 However, in this article, we shall concentrate on the misuse of prenatal technology, which has contributed to the skewed sex ratio in India.…”
mentioning
confidence: 99%
“…Despite some differences, similar findings have been reported in previous studies [5–7] indicating that the activities by the Ministry of Health and private sectors for the prevention of genetic disorders are well understood/accepted in the country. Research reports from the nine European countries, Georgia, Venezuela, and India showed that primary prevention measures have been implemented in these regions too [811]. However, the structure of the preventive strategies may vary by the region based on the population demands and financial sources.…”
Section: Discussionmentioning
confidence: 99%
“…[1119202122] There have been few studies on the applications of molecular cytogenetics for prenatal diagnostics in India. [1223] Moreover, there have been no publications in this area following the printing of the aforementioned articles, as per the MEDLINE search till December, 2010. The aim of the present study was to evaluate the accuracy of the rapid FISH technique for the early detection of numerical aberrations of chromosomes 13, 21, 18, X, and Y in interphase nuclei of uncultured amniocytes/cytotrophoblast cells in 163 high-risk pregnancies in comparison with conventional cytogenetics.…”
Section: Introductionmentioning
confidence: 99%